A multilevel analysis of contextual risk factors for intimate partner violence in Ghana - Cofie, Nicholas (International review of victimology, 2020)
While extant research suggests that context, structural socioeconomic and cultural factors matter in intimate partner violence research, quantitative research on the subject in sub-Saharan Africa, and in particular Ghana, has disproportionately focused on prevalence and individual level correlates of spousal violence. This research has ignored the role of the structural socioeconomic and cultural factors and contexts in understanding the causes and consequences of spousal violence in a setting where family life is heavily influenced by traditional norms and beliefs. These norms and beliefs may lead to inadequate and ineffective interventions geared at preventing or reducing spousal violence and its consequences. Guided by an integrated theoretical approach, this study addresses these issues by estimating a multilevel logistic regression model where the effects of both individual and community level risk factors for spousal violence are assessed. Data for the study come from the Ghana Demographic and Health Survey and the Ghana Population and Housing Census. The findings confirm the salient role of structural socioeconomic and cultural factors, such as patriarchal norms and residential instability, in the perpetration of spousal violence against women. Policy implications of these findings and directions for further research are discussed.